Dynamic behaviors of graphene platelets-reinforced metal foam piezoelectric beams with velocity feedback control - Chen, Jie; Zhang, Xinyue; Fan, Mingyang (Applied mathematics and mechanics, 2025)
Graphene platelets (GPLs)-reinforced metal foam structures enhance the mechanical properties while maintaining the lightweight characteristics of metal foams. Further bonding piezoelectric actuator and sensor layers on the surfaces of GPLs-reinforced metal foam beams enables active vibration control, greatly expanding their applications in the aerospace industry. For the first time, this paper investigates the vibration characteristics and active vibration control of GPLs-reinforced metal foam beams with surface-bonded piezoelectric layers. The constant velocity feedback scheme is used to design the closed-loop controller including piezoelectric actuators and sensors. The effects of the GPLs on the linear and nonlinear free vibrations of the beams are numerically studied. The Newmark- β method combined with Newton’s iteration technique is used to calculate the nonlinear responses of the beams under different load forms including harmonic loads, impact loads, and moving loads. Additionally, special attention is given to the vibration reduction performance of the velocity feedback control on the responses of the beam.